Beyond Romanization in Roman Athens: provincial culture and modes of integration in the decree IG II² 1035 - Morales, Fabio Augusto (Romanitas - Revista de Estudos Grecolatinos, 2018)
This paper discusses the ‘Romanization debate’ from the viewpoint of the Greek-speaking Roman provinces, taking as a case study the Athenian sanctuaries mentioned in the ‘Augustan’ decree for the restoration of Attic sanctuaries (IG II² 1035). After a brief discussion on the twists of the Romanization paradigm, the paper explores the relations between memory, culture and power implicated in the restorations, arguing that, rather than decide between ‘cultural resistance’ or ‘submission’ explanations, we should focus on the overlapping modalities of integration.
Keywords: Augustan Athens; Romanization; Decree IG II² 1035